The heartbeat of Wounded Knee : life in Native America - Keenan, Sheila (Viking, 2022)
Chronicles the history of Native American resilience against U.S. government attempts to erase their cultures and pasts throughout the twentieth century. Highlights and celebrates Native American success in preserving their languages, cultures, and their existence as a distinct people.